An introductory study of perceptual marginality in Slovakia - Mikuš, Roman; Máliková, Lucia; Lauko, Viliam (Bulletin of Geography. Socio-economic Series, 2016)
The existence of marginal regions is closely linked to the socio-spatial polarisation of our society. Especially in the post socialist countries, including Slovakia, which have undergone significant social and economic transformation, spatial polarisation and related regional disparities have become a relevant issue across multidisciplinary academic research. This study focuses on similarities and differences in defining the marginality from two different perspectives - one that is based on quantification of statistical data and another based on individual perception of marginality from the position of local mayors. Local mayors, the main figures of the local governance, have in the Slovak system of administration huge responsibility in the development of communes and a great opportunity to improve the status of certain communes, especially those marginal. At the same time this study investigates how the political affiliation and political support affect their competencies and activities in relation to the marginal position of their commune.